Certain integral inequalities involving tensor products, positive linear maps, and operator means - Pattrawut Chansangiam (My University, 2016)
We present a number of integral inequalities involving tensor products of continuous fields of bounded linear operators, positive linear maps, and operator means. In particular, the Kantorovich, Grüss, and reverse Hölder-McCarthy integral inequalities are obtained as special cases.
Keywords: Operator (biology); Linear operators; Mathematical Inequalities and Applications